Electrical, kinetic and photoelectrical properties of CuAlMnMg shape memory alloy/n-Si Schottky diode - Canbay, C. Aksu; Tataroglu, A.; Dere, A.; Al-Sehemi, Abdullah G.; Karabulut, Abdulkerim; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2021)
In this study, the copper-aluminum-manganese-magnesium (Cu-Al-Mn-Mg) shape memory alloy was utilized for the fabricated CuAlMnMg/n-Si/Al structure. The electrical characteristics of the diode were examined by using illumination intensity and frequency dependent current and admittance measurements. Basic electrical parameters such as barrier height (phi b0), ideality factor (n), and series (Rs) and shunt (Rsh) resistances of the generated diode were obtained from the measured current-voltage (I-V) data using thermionic emission (TE) theory. Illumination impact on the diode parameters indicate that the device displays photoconducting behavior. Furthermore, the phi b0 value was established from Norde method. There is a good agreement between phi b0 values acquired from conventional I-V and Norde method. It was observed that the rise in the applied illumination intensity increased the values of Rs and Rsh. In addition, the ad-mittance (Y=G+i omega C) measurements were carried out in a wide frequency range. As a result of the experi-mental measurements, it has been shown that the produced CuAlMnMg/n-Si Schottky diode can be operated in optoelectronic practices, especially as a photodiode. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Photodiode; Illumination intensity; Shape memory alloy; Kinetic parameters; Frequency